Therapeutics Role of Chandra Anulom-Vilom (CAV) Pranayama in Essential Hypertension: A Hypothesis (Janaki Medical College Journal of Medical Science, 2025)
Yoga is becoming increasingly popular for treating various health issues. One important part of yoga is Pranayama, or controlled breathing, which has caught the attention of researchers. Slow Pranayama techniques like Savitri, Sitkari, Anuloma Viloma, and Nadisuddhi (Alternate Nostril Breathing) are well known.  Some of these techniques are especially noted for their therapeutic benefits, including Nadisodhan (Alternate Nostril Breathing), Surya Anulom Vilom (SAV), and Chandra Anulom Vilom (CAV), also called Right nostril breathing (RNB) and Left Nostril Breathing (LNB) respectively. CAV also called left nostril breathing surges parasympathetic tone and inhibits sympathetic activities. Here, author hypothesized that CAV can reduce blood pressure and have therapeutics role in hypertensive patients. Proposed CAV technique can be used as therapy to reduce BP among Hypertensive patients. This has to be established with more extensive evidence-based researches which is under process. This paper, focuses on the therapeutic uses of these pranayama methods, especially CAV. Several researches showed that CAV decreases BP, HR and RR.